GRAMMAR CATEGORIES AND VOCABULARY FORM OF ADJECTIVES IN LATIN LANGUAGE (Journal of Universal Science Research, 2024)
This abstract tells about the adjectives and the groups of adjectives in Latin and some vocabulary and categories of the adjectives. We also get to know about adjective-noun agreement and adjective declensions of some Latin words.